Influence on fine lead–zinc tailings solidified/stabilised by clinker-free slag-based binder. Issue 6 (December 2022) - Zhao, Tong; Zhang, Siqi; Yang, Huifen; Ni, Wen; Li, Jia; Zhang, Ge; Teng, Guoxiang
Abstract: This study applied steel slag (SS), blast furnace slag (BFS), flue gas desulfurised (FGD) gypsum and fly ash (FA) as clinker-free cementitious materials for fine lead–zinc tailing (LZT) backfillings and investigated the mechanism of Pb and Zn immobilisation in tailings. In a binder with 42%, 42% and 16% of SS, BFS and FGD gypsum, respectively, the binder-to-tailings ratio was 1:4. Additionally, the slurry concentration was 78%, resulting in unconﬁned compressive strength values of 0.89, 6.47 and 11.03 MPa after 7, 28 and 56 d, respectively, and fluidity of 230 mm. After 56 d of curing, the leaching concentration of Pb and Zn became 0.34 and 0.63 μg/L, respectively, and the immobilisation efficiency and the bioavailability reduction efficiency of Pb and Zn were 99% and 90%, respectively, which are lower than the underground class III water standard. Additionally, the double salt effect was a crucial reason for the excellent immobilisation properties of Pb and Zn. Micro-analysis indicated that anglesite, minrecordite and Pb[Fe3 (SO4 )2 (OH)6 ]2 formed during the hydration process with their solubility products (Ksp) at 1.622 × 10 −8, 1 × 10 −20 to 1 × 10 −16 and 1 × 10 −25.5 at 25 °C. Furthermore, the residues of Pb and Zn in the morphological analysis increased from 29% and 37% (the original) to 65% and 67% (curing 56 d), corresponding to the increasing binding energy and content of Zn–O and Pb–O. Moreover, calcium–silicate–hydrate gel and ettringite appeared in the solidified samples, with a high degree of cementation, as the hydration age increased. Highlights: The 28d, 56d compressive strength of G9 reaches 6.47 MPa and 11.03 MPa. G9′s filling performance and leaching risk are controllable. The residues of Pb/Zn are consistent with the Zn/Pb-O binding energy. Anglesite, Minrecordite and Pb[Fe3 (SO4 )2 (OH)6 ]2 phases are probably formed at 56 d.